Effect of 2% Lidocaine and 1:80000 Epinephrine on Heart Rate and Blood Oxygen Saturation During Inferior Alveolar Nerve Block and Gow-Gates Block:A Clinical Trial - M Vatanpour; N Roghanizad; D bineshmarvasti; R Hosseini; P Mohebbi (Islamic Azad University, 2017)
Background and Aim: The Gow-Gates (GG) block and the inferior alveolar nerve block (IANB) can be used interchangeably for anesthetizing mandibular molars. The aim of this study was to compare these two injections in root canal therapy of mandibular molars with regard to heart rate (HR) and blood oxygen saturation (BOS) changes. Materials and Methods: Thirty patients between the ages of 18-70 years having mandibular molars on both sides of their jaw and in need of root canal therapy were recruited after signing a consent form. The patients' HR and BOS were measured 5 minutes before and immediately, 2, 5, 10, 15, and 20 minutes after injection by using a pulse oximeter. Paired t-test and Friedman test were used for statistical analysis of the data. Results: This study was done on 30 patients (60 teeth). The results of HR and BOS showed no significant differences between the two injection techniques (P=0.6 and 0.7, respectively). Also, HR and BOS in each group were not significantly changed during the follow-ups (P=0.7 and 0.6, respectively). Conclusion: According to the results, IANB and GG block by using 2% lidocaine and 1:80000 epinephrine had no significant different effects on HR and BOS.